2013
DOI: 10.1002/lpor.201200118
|View full text |Cite
|
Sign up to set email alerts
|

Optical isotropization of anisotropic wurtzite Al-rich AlGaN via asymmetric modulation with ultrathin (GaN) m /(AlN) n superlattices

Abstract: Symmetric anisotropy in wurtzite semiconductors, e.g., AlGaN, has led to the significant optical anisotropy that is rather difficult to resolve. Here, a novel scheme for achieving optical isotropization in Al‐rich AlGaN through the introduction of additional asymmetric elements is demonstrated to compensate the native asymmetry. Asymmetric modulation of alloy composition and periodicity of (GaN)m/(AlN)n superlatices was proposed with first‐principles simulations. Results showed that the compensation for the c‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…One can see that for the n-type layer emission at approximately 265 nm, the LEE enhancement ratios are approximately 2.4 and 9.2 for the TE and TM polarization states, respectively. Previous investigation indicated that even for compressively grown AlGaN MQWs, strongly TE-polarized emission can be observed at wavelengths as short as 240 nm [30]. Thus, it is reasonable that the LEE enhancement of a mixture of TE and TM states is approximately 2.8.…”
Section: Resultsmentioning
confidence: 96%
“…One can see that for the n-type layer emission at approximately 265 nm, the LEE enhancement ratios are approximately 2.4 and 9.2 for the TE and TM polarization states, respectively. Previous investigation indicated that even for compressively grown AlGaN MQWs, strongly TE-polarized emission can be observed at wavelengths as short as 240 nm [30]. Thus, it is reasonable that the LEE enhancement of a mixture of TE and TM states is approximately 2.8.…”
Section: Resultsmentioning
confidence: 96%
“…In previous study on the optical anisotropy in AlGaN, it was recognized that, in contrast to the Ga-rich AlGaN, the VBM is dominated by the CH band in Al-rich AlGaN instead of HH/LH bands (Fig. 8b ) 108 , 109 . With respect to c -axis, the CH band at VBM is composed of p z -orbitals with odd symmetry.…”
Section: Manipulation Of Atomic Orbital Couplingmentioning
confidence: 94%
“… 105 , © 2011 AIP Publishing, b ref. 108 , © 2013 John Wiley and Sons; c and d : ref. 113 , © 2020 Springer Nature …”
Section: Manipulation Of Atomic Orbital Couplingmentioning
confidence: 99%
See 2 more Smart Citations